Pengaruh Profitabilitas dan Nilai Perusahaan terhadap Pengambilan Keputusan Investasi dengan Good Corporate Governance sebagai Moderasi - Charissa Moren Armanto Putri (Moneter : Jurnal Ekonomi dan Keuangan, 2026)
This study aims to analyze the effect of profitability measured by Return on Assets (ROA), Return on Equity (ROE), and Earning Per Share (EPS) and firm value measured by Price to Book Value (PBV) on investment decision-making, with Good Corporate Governance (GCG) as a moderating variable. This research is conducted against the backdrop of investment fluctuations in the Indonesian banking sector during the 2019-2024 period due to post-pandemic dynamics. Utilizing a quantitative method with a purposive sampling technique on 26 banking companies listed on the Indonesia Stock Exchange (IDX), the data were analyzed using multiple linear regression and Moderated Regression Analysis (MRA). The results indicate that profitability and firm value have a positive and significant effect on investment decisions, proving that investors highly consider profitability and market appreciation when allocating capital for investment. Furthermore, GCG was found to significantly strengthen the influence of both variables on investment decisions, reinforcing that good corporate governance can enhance investor confidence in a company's financial signals amid market uncertainty.